1996
DOI: 10.1159/000227563
|View full text |Cite
|
Sign up to set email alerts
|

Local Hyperthermia, Radiation, and Chemotherapy in Locally Advanced Malignancies

Abstract: Tumor size is a significant prognostic variable for attaining complete regression (CR) with local hyperthermia (HT) and radiation therapy (RT). The addition of weekly chemotherapy was evaluated to improve the efficacy of thermoradiotherapy in poor-prognosis lesions (i.e. ≥1 cm2 or ≥ 14 cm3) which have an expected CR rate of ∼ 30 ± 8%. Patients were entered into a two-arm phase-II study: arm 1 = breast cancer (10 patients), ifosfamide (1.5 g/m2) + epirubicin (20 mg/m2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 15 publications
0
26
0
Order By: Relevance
“…Application of hyperthermia to thermally target the elastin-like polypeptide therapeutic carriers may offer further advantages in the treatment of solid tumors. Specifically, hyperthermia preferentially increases the permeability of tumor vasculature compared with normal vasculature (18,19), and therefore it may further enhance the delivery of drugs to tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Application of hyperthermia to thermally target the elastin-like polypeptide therapeutic carriers may offer further advantages in the treatment of solid tumors. Specifically, hyperthermia preferentially increases the permeability of tumor vasculature compared with normal vasculature (18,19), and therefore it may further enhance the delivery of drugs to tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Of these 17 cases, 7 had lymph node metastases measuring ≥6 cm, but the results for this subgroup have not been given in detail. In a study by Feyerabend et al [6], a patient with a large (13 cm) cervical lymph node metastasis showed a PR following treatment with a combination of radiotherapy (40 Gy), four sessions of hyperthermia, and four cycles of chemotherapy (CDDP, 40 mg/m 2 ) during the 15-month follow-up. Serin et al [7]recently reported that they treated 7 cases of N 3 lymph node metastasis by a combination of radiotherapy (60–70 Gy), hyperthermia (5– 8 sessions), and chemotherapy (5–6 cycles of CDDP, 30 mg/m 2 ), and that 2 of these patients were alive at the time of the last follow-up, resulting in a survival rate of 28.6%.…”
Section: Discussionmentioning
confidence: 99%
“…However, no therapeutic methods have been established for highly advanced cases and cases with cervical lymph node metastases, and results of treatment of advanced cases have been unsatisfactory. Patients with cervical lymph node metastasis are particularly difficult to treat, although these tumors may respond to a combination of radiotherapy and hyperthermia [1, 2, 3, 4, 5, 6, 7]. Cervical lymph node metastases can exceed 6 cm in largest diameter (termed N 3 in the node metastasis classification of the UICC) [8], although such large nodal metastases are not frequently seen.…”
Section: Introductionmentioning
confidence: 99%
“…This can be accomplished using different approaches, but the idea is to destroy all the tissue in a radius around the tumor while leaving the remaining breast unaltered, using different energy sources (such as laser, ultrasound or microwave) for interstitial hyperthermia or cryosurgery (158 ± 164). This approach has been used in a small number of patients (161,163,164) and is currently under investigation. The goal is to treat small breast cancers (5 10 mm) following stereotactic biopsy with a probe placed through a 2-mm entrance site and no other visible surface change.…”
Section: In Situ Destruction Of the Primary Breast Cancermentioning
confidence: 99%